Efektivitas Model Pembelajaran Picture and Picture dalam Baca Tulis Qur’an Kelas 5 di SDN Lagadar 01 Margaasih - Dwi Nurtifa; Dedih Surana; Huriah Rachmah (Bandung Conference Series: Islamic Education, 2024)
Abstract. Effectiveness of the Picture and Picture Learning Model in Reading writing the Qur’an Class V SDN Lagadar 01 This research discusses the effectiveness of using the picture and picture learning model in determining the effectiveness of students in Islamic Religious Education subjects in reading the Al-Qur'an at SDN Lagadar 01 Margaasih. This research uses quantitative research of the type quasi-experimental design or quasi-experiment. Calculations use 80 samples consisting of 2 classes. The results of this research are that the use of the picture and picture learning model is more effective in increasing students' BTQ scores in the Islamic Religious Education subject at SDN Lagadar 01 Margaasih with the topic of discussion being Tajwid Science. This is based on the results of the t test on both groups with the results obtained that class 5 A had a better average score with a value of 77.89 while class 5 B which previously had an average above class 5 A became below class 5 A with the average value is 64.88. It can be seen that the average score for class 5 A after the experiment was carried out increased by 51% from the average score obtained before the implementation of the picture and picture model. Abstrak. Penelitian ini membahas tentang efektivitas penggunaan model pembelajaran picture and picture dalam mengetahui keefektivan siswa pada mata pelajaran Pendidikan Agama Islam dalam membaca Al-Qur’an di SDN Lagadar 01 Margaasih. Penelitian ini bertujuan untuk mengetahui keefektifan model pembelajaran picture and picture dalam meningkatkan hasil belajar siswa pada mata pelajaran Pendidikan Agama Islam. Penelitian ini menggunakan penelitian kuantitatif jenis quasi eksperimen design atau eksperimen semu. Perhitungan menggunakan 80 sampel yang terdiri dari 2 kelas. Hasil dari penelitian ini adalah penggunaan model pembelajaran picture and picture lebih efektif dalam meningkatkan nilai BTQ siswa pada mata pelajaran Pendidikan Agama Islam di SDN Lagadar 01 Margaasih dengan pokok pembahasan tentang Ilmu Tajwid. Hal tersebut berdasarkan dari hasil pengujian t terhadap kedua kelompok dengan hasil yang diperoleh bahwa kelas 5 A memiliki jumlah nilai rata rata yang lebih baik dengan nilai 77,89 sedangkan kelas 5 B yang sebelumnya memiliki rata rata diatas kelas 5 A menjadi dibawah kelas 5 A dengan nilai rata rata 64,88. Terlihat bahwa nilai rata rata kelas 5 A setelah dilakukannya experimen tersebut meningkat 51% dari nilai rata rata yang didapat sebelum adanya penerapan model Picture and Picture.